Kajian Tafsir Tahlili pada Surat Al-Furqan - Haris, Abdul Rauf; Habibi, Habibi (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2020)
Allah Ta’ala has sent down His blessed book so that people who believe in it to pay attention or sprinkle His verses. As for the background of writing this thesis, it starts from the verse of Allah which uses livestock to liken the polytheists. human beings who in fact have intellect and position on earth are likened to livestock, the Qur’an with its beautiful arrangement of words full of wisdom of course there is a lesson in the parable. Therefore, the formulation of the problem in this study is what is the wisdom in the parable. This type of research is in the form of a library, so the data source data is in the form of library material based on primary and secondary sources. The method used is the method of tahlili which in this study describes the content of the verses studied such as reasonable letter by letter, reasonable verse by verse, vocabulary meaning, asbab an-nuzul and interpretation according to the scholars of tafsir. From the research that has been done can be obtained a conclusion that the wisdom in the parable of livestock with the polytheists is to give a lesson to humans how important it is to always keep lust so as not to exceed the limits that make the perpetrator can not receive the light of truth and be grateful for the blessings of guidance in Islam. using the hearing and intellect that Allah Ta'ala has bestowed in order to understand the verses of the Qur'an. Abstrak Allah Ta’ala telah menurunkan kitabnya yang berkah supaya manusia yang meyakininya untuk memperhatikan ataupun mentadaburi ayat-ayat-Nya. Adapun latar belakang penulisan skripsi ini berawal dari ayat Allah yang menggunaka hewan ternak untuk mengumpamakan orang-orang musyrik. manusia yang pada hakikatnya mempunyai akal dan kedudukan di muka bumi diserupakan dengan hewan ternak, Al-Qur’an dengan susunan lafaznya yang indah penuh hikmah tentu terdapat pelajaran didalam perumpamaan tersebut. Oleh karena itu, rumusan masalah dalam penelitian ini apa hikmah dalam perumpamaan tersebut. Jenis penelitian ini berbentuk kepustakaan, maka data sumber datanya ialah berupa bahan pustaka berdasarkan sumber primer dan sekunder. Metode yang digunakan adalah metode tahlili dimana dalam penelitian ini menguraikan kandungan dari ayat yang dikaji seperti munasabah surat dengan surat, munasabah ayat dengan ayat, pengertian kosakata, asbab an-nuzul dan penafsiran menurut para ulama tafsir. Penelitian mendapat sebuah kesimpulan bahwa hikmah dalam perumpamaan hewan ternak dengan orang musyrik ialah memberikan pelajaran kepada manusia betapa pentingnya senantiasa menjaga hawa nafsu agar tidak melampaui batas yang menjadikan pelakunya tidak bisa menerima cahaya kebenaran dan mensyukuri nikmat hidayah dalam agama islam dengan cara menggunakan pendengaran dan akal yang Allah Ta’ala anugrahkan guna memahami ayat-ayat Al-Qur’an.